The Measure of Civilization : How Social Development Decides the Fate of Nations. - Morris, Ian (Princeton University Press, 2013)
In the last thirty years, there have been fierce debates over how civilizations develop and why the West became so powerful. The Measure of Civilization presents a brand-new way of investigating these questions and provides new tools for assessing the long-term growth of societies. Using a groundbreaking numerical index of social development that compares societies in different times and places, award-winning author Ian Morris sets forth a sweeping examination of Eastern and Western development across 15,000 years since the end of the last ice age. He offers surprising conclusions ab.